Mana Deva I: The First Recorded Unifier of Nepal - Subedi, Kulmandan (Unity Journal, 2024)
This paper gives an insight into the efforts of King Mana Deva I as the first recorded Unifier of Nepal. The objective of this paper is to highlight various dimensions of the unification efforts of Mana Deva I. The writer has attempted to put forward the evidence and findings of historians and archeologists who have come to the common understanding that Mana Deva I was the first recorded unifier of ancient Nepal. Analytical approach has been used for the research of his life, leadership, and achievements. Studies of the inscriptions, important documents, books, journals, and articles have been made relating to Mana Deva. He provided the first authentic history of Nepal extending from Brahmaputra in the east to Kashmir in the west. When Mana Deva I was only 12 years old, his father Dharma Deva died. Instead of burning herself with her dead husband’s corpse as Sati, Mana Deva’s mother, Rajyawati, assisted her son in his reign. Mana Deva, with the assistance of his mother and maternal uncle, began a military unification effort both in the east and west. The success of the military unification effort provided an opportunity for the king to unify the nation in other aspects as well. Mananka- the coin introduced by the king led to economic unification; Managriha- his royal palace provided a center for administrative unification; and his religious synergetic activities led to cultural unification. The leadership of Mana Deva I greatly impacted and influenced the later Lichhavi kings and hence, Lichhavi's rule is considered the golden period of ancient Nepali history.